A Precision Medicine Approach to Dosing and Management of Continuous Renal Replacement Therapy for Acute Kidney Injury - KELLY, YVELYNNE PATRICE (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2020)
Background: Despite decades of research, the mainstay of treatment for severe acute kidney injury (AKI) in the critical care setting remains renal replacement therapy in the form of dialysis. Continuous renal replacement therapy (CRRT) poses the risk for unintended adverse events, which in general have been largely under-studied in critical care and nephrology; including depletion of phosphorus, amino acids, catecholamines and trace elements. CRRT also clears the circulation of medications, and dosing guidelines in general are not well established for CRRT. Aims: Higher intensity CRRT has been studied as a potential therapeutic advance for the treatment of severe AKI by increasing middle molecule clearance, enhancing acid-base buffering and potentially reducing pro-inflammatory cytokines in the setting of sepsis and shock; however it has never been shown to have a mortality benefit. I hypothesised that compared to standard intensity CRRT, higher intensity CRRT leads to greater haemodynamic instability and prolonged mechanical ventilation due to the unregulated removal of small solutes such as phosphate, amino acids, trace elements and medications, and that hypotension on CRRT leads to greater tubular injury, measured with biomarkers specific to ischaemic renal tubular injury, and prolonged time to renal recovery. I also assessed the effects of timing of initiation and discontinuation of RRT for AKI on patient outcomes in a randomised controlled trial and performed a systematic review and meta-analysis on the effect of CRRT on haemodynamic instability in critically ill patients. Methods: I performed secondary statistical analyses of the Acute Renal Failure Trial Network (ATN) trial, which compared intensive versus less intensive RRT dosing for critically ill patients with AKI, during which I assessed the frequency of and risk factors for hypotensive events on CRRT according to treatment dose. I also assessed the effect of intensity of CRRT dosing on time to extubation from mechanical ventilation. I measured plasma KIM-1, a renal-specific biomarker of ischaemic tubular injury, in stored blood samples taken from patients during the trial, to assess the ability of plasma renal biomarkers to predict patient outcomes in AKI-RRT. I performed a systematic review and meta-analysis on the effect of CRRT on haemodynamic outcomes in AKI. Finally, I developed evidence-based guidelines for discontinuation of RRT in the setting of recovery from AKI, as well as performing a narrative review on optimising vascular access for AKI-RRT. Results: CRRT treatment dose was not a significant risk factor for treatment associated hypotension; nor was ultrafiltration rate. Hypocalcaemia < 1.02 mmol/L was associated with a significantly increased risk of CRRT-associated hypotension. CRRT treatment dose was associated with a significantly longer time to first extubation from mechanical ventilation. Serum phosphate depletion occurred more frequently for patients randomised to higher intensity RRT. For those patients who were successfully extubated initially, there was a significantly higher probability of re-intubation in those randomised to more more-intensive RRT (19% versus 10%; p = 0.03). Plasma KIM-1 was associated with increased risk of 28-day mortality (odds ratio 1.15; 95% CI 1.03-1.29) and decreased likelihood of renal recovery (odds ratio 0.75; 95% CI 0.63-0.9). There was significant heterogeneity present for all outcomes from our meta-analysis of haemodynamic outcomes on CRRT apart from a finding of reduced mean arterial pressure with CVVHD using lactate-buffered dialysate compared to bicarbonate-buffered dialysate. An evaluation of a clinical decision support system for initiation of RRT in the setting of AKI - the Standardised Clinical Assessment and Management Plan (SCAMP) - did not impact the primary outcome of in-hospital, 30-day or 60-day mortality, but did result in a significantly reduced ICU and hospital length of stay for patients with AKI, as well as a reduced 30-day hospital readmission rate. A review of literature including the results of a prospective cohort study performed at Brigham and Women?s Hospital in 2017 (Mendu., 2017) showed that tunnelled dialysis catheters (TDC) use is associated with decreased mechanical and infectious complications, as well as improved dialysis delivery by comparison with use of non-tunnelled equivalents. Conclusions: An individualised approach to CRRT prescribing and management, using evidence-based guidelines, is needed to reduce the risk of adverse events associated with this supportive therapy for severe AKI. In this thesis I have identified modifiable aspects of the CRRT prescription which increase the risk of treatment-associated adverse events. Further dedicated clinical trials will be needed to assess whether optimising these CRRT treatment characteristics improve the risk of adverse outcomes for critically ill patients with AKI.
APPROVED
Keywords: Acute kidney injury; Intensive care; Renal replacement therapy